Cell permeabilization by poliovirus 2B viroporin triggers bystander permeabilization in neighbouring cells through a mechanism involving gap junctions - Madan Renes, Vanesa; Redondo Rodríguez, Natalia; Carrasco, Luis (Cellular microbiology, 2010)
Poliovirus 2B protein is a well-known viroporin implicated in plasma membrane permeabilization to ions and low-molecular-weight compounds during infection. Translation in mammalian cells expressing 2B protein is inhibited by hygromycin B (HB) but remains unaffected in mock cells, which are not permeable to the inhibitor. Here we describe a previously unreported bystander effect in which healthy baby hamster kidney (BHK) cells become sensitive to HB when co-cultured with a low proportion of cells expressing poliovirus 2B.